Kebijakan Hukum dalam Pemberantasan Pelaku Online Romance Fraud di Ruang Maya - Fikri, Ahmad Ma'mun (CIC Lembaga Riset dan Konsultan Sosial, 2024)
Online romance fraud is a form of cybercrime that exploits emotional manipulation to obtain financial gain or personal information. This phenomenon has become increasingly prevalent with the rise of internet usage in Indonesia. This study aims to evaluate Indonesia’s legal policies, such as the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP), in addressing this issue, as well as to identify regulatory gaps and existing challenges. The findings are expected to provide recommendations for updating legal policies to be more adaptive to technological advancements, ensuring better protection for the public against online romance fraud. This research employs a qualitative approach, utilizing a normative juridical method that focuses on analyzing relevant laws and assessing their applicability in cases of online romance fraud. Secondary data from various legal literatures, case reports, and national surveys are used to evaluate the effectiveness of current regulations. The study finds that Indonesia’s legal policies on online romance fraud still have limitations, as the UU ITE and Article 378 of the KUHP do not specifically regulate crimes based on emotional manipulation in online relationships. Regulatory updates are needed to include clearer definitions, stricter sanctions, and effective reporting mechanisms, supported by digital literacy initiatives and international cooperation. Collaboration with digital platforms to enhance AI-based security measures and strengthen law enforcement capacity is crucial in creating a safer digital space.